2010
DOI: 10.1088/0953-2048/23/3/034015
|View full text |Cite
|
Sign up to set email alerts
|

Application of textured highly alloyed Ni–W tapes for preparing coated conductor architectures

Abstract: An epitaxial Y2O3/YSZ/CeO2 buffer architecture has been prepared on cube textured Ni–5 at.%W, Ni–7.5 at.%W and Ni–9 at.%W tapes using pulsed laser deposition. The buffer layer growth was studied in detail and revealed a good texture transfer throughout the structure on the global as well as on the local scale. YBCO (yttrium barium copper oxide) layers were successfully deposited on the buffered tapes, showing an in-plane texture spread of about 7°. Microstructural investigations revealed clear interfaces and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
4
10
0
Order By: Relevance
“…Note also that coated conductors fabricated by this technology are strongly magnetic because of the ferromagnetic substrate, but efforts to mitigate this problem by developing NiW alloys with depressed or even completely suppressed ferromagnetism (depending on the W content) are under way and look promising. 107 The second processing route follows a different path (Fig. 33).…”
Section: High Temperature Superconductorsmentioning
confidence: 99%
“…Note also that coated conductors fabricated by this technology are strongly magnetic because of the ferromagnetic substrate, but efforts to mitigate this problem by developing NiW alloys with depressed or even completely suppressed ferromagnetism (depending on the W content) are under way and look promising. 107 The second processing route follows a different path (Fig. 33).…”
Section: High Temperature Superconductorsmentioning
confidence: 99%
“…energy harvesters, would benefit from the use of a flexible substrate. Flexibility can be achieved by using organic substrates [4] Developments in the processing of high-temperature superconducting tapes have shown that cube-textured Ni-based alloys can be used as templates for growing preferentially oriented ceramic thin films [7]. The present work was undertaken as a proof-of-concept study to demonstrate that this approach can also be applied to the manufacture of textured KNN films directly on flexible, electrically conductive substrates.…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, alloying also plays a fundamental role in both the generation of the cube texture and the temperature region where this texture is stable [ 3 ]. Alloying with refractory metals, such as Mo, W, Nb and Ta, or with Cr, enabled achievement of thermally stable quality texture at high temperatures, up to and above 800 °C [ 4 , 5 , 6 , 7 ]. In addition, these Ni alloys feature an increase of mechanical strength and a weakening of the ferromagnetism of pure Ni.…”
Section: Introductionmentioning
confidence: 99%